Robotic Versus Open Liver Resection in Hepatocarcinoma: Surgical and Oncological Outcomes. Issue 4 (August 2021) - Pesi, Benedetta; Bencini, Lapo; Moraldi, Luca; Tofani, Federica; Batignani, Giacomo; Bechi, Paolo; Farsi, Marco; Annecchiarico, Mario; Coratti, Andrea
Abstract : Background: Minimally invasive approaches are spreading in every field of surgery, including liver surgery. However, studies comparing robotic hepatectomy with the conventional open approach regarding oncologic outcomes for hepatocellular carcinoma are limited. Materials and Methods: We retrospectively reviewed demographics characteristics, pathologic features, surgical, and oncological outcomes of patients who underwent robotic and conventional open liver resection for hepatocellular carcinoma. Results: No significant differences in demographics features, tumor size, tumor location, and type of liver resection were found. The morbidity rate was similar, 23% for the open group versus 17% of the robotic group ( P =0.605). Perioperative data analysis showed a greater estimated blood loss in patients who underwent open resection, if compared with robotic group ( P =0.003). R0 resection and disease-free resection margins showed no statistically significant differences. The 3-year disease-free survival of the robotic group was comparable with that of the open group (54% vs. 37%; P =0.592), as was the 3-year overall survival (87% vs. 78%; P =0.203). Conclusions: The surgical and the oncological outcomes seem to be comparable between minimally invasive and open hepatectomy. Robotic liver resections are effective, and do not compromise the oncological outcome, representing a reasonable alternative to the open approach.